Peningkatan Sistem Penerangan Jalan dan Pengelolaan Sanggar Waringin di Desa Soneyan, Kabupaten Pati - Muhammad Atiq; Danang Hendrawan; Rizal Agri Wahyuadi; Raka Dian Mahardi; Sigit Prakosa AN (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service project aims to improve the quality of street lighting around the Waringin Tunggal Studio, located in Soneyan Village, Pati Regency. As part of efforts to improve community comfort and safety, this project focuses on addressing the issue of inadequate lighting that can impact community activities, particularly at night. Inadequate lighting around the studio creates discomfort and reduces the sense of security for both studio users and the local community. The project began with a thorough inspection of the lighting conditions around the studio. The next step was to design technical solutions to improve the existing lighting system, including increasing the number of lamps and using more efficient types of lamps in terms of energy consumption and light distribution. Furthermore, good collaboration with village officials and other relevant parties was crucial for the smooth implementation of this project. The improvement process was carried out with a focus on energy efficiency and durability, ensuring long-term benefits. The results of this project showed a significant improvement in the quality and coverage of lighting around the Waringin Tunggal Studio. This improvement not only increased comfort but also increased the sense of security for studio visitors and the surrounding community. Access to the studio at night has become easier and safer, positively impacting the arts and cultural activities held there. A post-event evaluation showed increased community participation in the studio's evening events. This success demonstrates that improved lighting can encourage community participation in community activities. Going forward, it is hoped that this activity can be enhanced by utilizing renewable energy, such as solar power, to ensure optimal lighting even during power outages, thus ensuring the desirability of this activity in the future.